Decellularization of porcine articular cartilage explants and their subsequent repopulation with human chondroprogenitor cells. (March 2015) - Luo, Lu; Eswaramoorthy, Rajalakshmanan; Mulhall, Kevin J.; Kelly, Daniel J.
Abstract: Engineering tissues with comparable structure, composition and mechanical functionality to native articular cartilage remains a challenge. One possible solution would be to decellularize xenogeneic articular cartilage in such a way that the structure of the tissue is maintained, and to then repopulate this decellularized matrix with human chondroprogenitor cells that will facilitate the reconstitution, maintenance and eventual turnover of the construct following implantation. The overall objective of this study was to develop a protocol to efficiently decellularize porcine articular cartilage grafts and to identify a methodology to subsequently repopulate such explants with human chondroprogenitor cells. To this end, channels were first introduced into cylindrical articular cartilage explants, which were then decellularized with a combination of various chemical reagents including sodium dodecyl sulfate (SDS) and nucleases. The decellularization protocol resulted in a ~90% reduction in porcine DNA content, with little observed effect on the collagen content and the collagen architecture of the tissue, although a near-complete removal of sulfated glycosaminoglycans (sGAG) and a related reduction in tissue compressive properties was observed. The introduction of channels did not have any detrimental effect on the biochemical or the mechanical properties of the decellularized tissue. Next, decellularized cartilage explants with or without channels were seeded with human infrapatellar fat pad derived stem cells (FPSCs) and cultured chondrogenically under either static or rotational conditions for 10 days. Both channeled and non-channeled explants supported the viability, proliferation and chondrogenic differentiation of FPSCs. The addition of channels facilitated cell migration and subsequent deposition of cartilage-specific matrix into more central regions of these explants. The application of rotational culture appeared to promote a less proliferative cellular phenotype and led to an increase in sGAG synthesis within the explants. Rotational culture also appeared to promote higher cell viability and led to a more even distribution of cells within the channels of decellularized explants. To conclude, this study describes an effective protocol for the decellularization of porcine articular cartilage grafts and a novel methodology for the partial recellularization of such explants with human stem cells. Decellularized soft tissue explants that maintain their native collagen architecture may represent promising scaffolds for musculoskeletal tissue engineering applications.